Surgery along the embryological planes for colon cancer: a systematic review of complete mesocolic excision - Gouvas, Nikolaos; Agalianos, Christos; Papaparaskeva, Kleio; Perrakis, Aristotelis; Hohenberger, Werner; Xynos, Evaghelos (International Journal of Colorectal Disease, 2016)
Complete mesocolic excision (CME) for colonic cancer offers a surgical specimen of higher quality, with higher number of lymph nodes compared to conventional colectomy. However, evidence on oncological outcomes is limited. The aim of the present study is to review recent literature and provide more information regarding the effect of CME colectomy on short- and long-term outcomes.PubMed and MEDLINE databases were searched, and articles in English reporting data on CME were reviewed. Intraoperative events; postoperative morbidity and mortality; histopathological characteristics, including macroscopic assessment, number, and status of retrieved lymph nodes; and oncological outcomes were the end-points.Thirty-two studies were analyzed. As regards the macroscopic assessment, a larger specimen (p = 0.02) that contains a higher number of lymph nodes (p < 0.00001) is acquired after CME. Two studies report a higher disease-free survival, in stage I and II and particularly in stage III disease after CME. CME by laparoscopy offers comparable outcomes, as regards intraoperative blood loss and immediate postoperative morbidity and mortality rates. Specimen quality is similar after either approach, for cancers located at the right and left colon, but not at the transverse colon.There is strong evidence that CME offers a longer central pedicle that contains more lymph nodes than conventional surgery for colon cancer. CME represents the surgical background for the maximum lymph node harvest, an important quality marker for the surgical outcome. However, and according to present data, there is limited evidence that colectomy in terms of CME leads to improved long-term oncological outcomes.
EVALuna2:15245